The Role of the Skeletal Muscle Secretome in Mediating Endurance and Resistance Training Adaptations - Leuchtmann, Aurel B.; Adak, Volkan; Dilbaz, Sedat; Handschin, Christoph (Frontiers in Physiology, 2021)
Exercise, in the form of endurance or resistance training, leads to specific molecular and cellular adaptions not only in skeletal muscles, but also in many other organs such as the brain, liver, fat or bone. In addition to direct effects of exercise on these organs, the production and release of a plethora of different signaling molecules from skeletal muscle are a centerpiece of systemic plasticity. Most studies have so far focused on the regulation and function of such myokines in acute exercise bouts. In contrast, the secretome of long-term training adaptation remains less well understood, and the contribution of non-myokine factors, including metabolites, enzymes, microRNAs or mitochondrial DNA transported in extracellular vesicles or by other means, is underappreciated. In this review, we therefore provide an overview on the current knowledge of endurance and resistance exercise-induced factors of the skeletal muscle secretome that mediate muscular and systemic adaptations to long-term training. Targeting these factors and leveraging their functions could not only have broad implications for athletic performance, but also for the prevention and therapy in diseased and elderly populations.